Transformasi Digital Berkelanjutan UMKM Kuliner melalui Sistem Informasi E-Commerce Berbasis Web dalam Ekosistem Cerdas - Husni Faqih; Fandhilah Fandhilah; Mawadatul Maulidah; Nadiyah Hidayati; Nafisah Muazarah; Asna Mauhibah Maurani (LPPM Universitas Bina Sarana Informatika, 2026)
Sustainable digital transformation has become a strategic necessity for UMKM to improve efficiency and competitiveness in the digital economy era. This study aims to examine the implementation of a web-based e-commerce information system as part of digital transformation efforts at Bakehouse, a bakery and pastry UMKM. The main problems faced by the partner include manual sales and transaction recording, unintegrated order data, a high risk of recording errors, and limitations in generating accurate and timely sales reports. The research method used is a system development approach with the Waterfall model, which includes requirements analysis, system design, implementation, and testing stages. The system was developed using the Laravel framework and MySQL database and is equipped with features for managing products, categories, customers, order transactions, and periodic sales reports. The results show that the implementation of the web-based e-commerce information system improves operational efficiency, increases data recording accuracy, and facilitates monitoring and information-based decision making. The system functions not only as an online sales platform but also as an initial foundation for building a smarter business ecosystem and supporting sustainable digital transformation in culinary UMKM